2020
DOI: 10.1155/2020/6389368
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effects of Acupuncture on Hippocampal Functional Connectivity in aMCI with Hippocampal Atrophy: A Randomized Longitudinal fMRI Study

Abstract: Background. Acupuncture has been used to treat amnestic mild cognitive impairment (aMCI) for many years in China. However, the long-term effects of continuous acupuncture treatment remained unclear. Objective. We aimed to explore the long-term effects of continuous acupuncture treatment on hippocampal functional connectivity (FC) in aMCI. Methods. Fifty healthy control (HC) participants and 28 aMCI patients were recruited for resting-state functional magnetic resonance imaging (fMRI) at baseline. The 28 aMCI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…This study compared fMRI from 50 cognitively unimpaired participants to 28 with amnestic MCI. 46 China ADNI is now launching a larger, randomized controlled trial to further study Siguan acupoints and MCI progression. The study includes measurements of amyloid and tau in blood and/or CSF, a cognitive testing battery, as well as MRI and 18 F-FDG-PET in accordance with ADNI protocols.…”
Section: China Adnimentioning
confidence: 99%
See 1 more Smart Citation
“…This study compared fMRI from 50 cognitively unimpaired participants to 28 with amnestic MCI. 46 China ADNI is now launching a larger, randomized controlled trial to further study Siguan acupoints and MCI progression. The study includes measurements of amyloid and tau in blood and/or CSF, a cognitive testing battery, as well as MRI and 18 F-FDG-PET in accordance with ADNI protocols.…”
Section: China Adnimentioning
confidence: 99%
“…A randomized, controlled trial by China ADNI found that 6 months of consistent acupuncture treatment delayed MCI disease progression. This study compared fMRI from 50 cognitively unimpaired participants to 28 with amnestic MCI 46 …”
Section: Worldwide Adnimentioning
confidence: 99%
“…Brain functional network, as one type of the complex networks in statistical physics, is a demonstration of the temporal correlations between different brain areas in the processes of neural physiological events [ 16 ]. It has become one of the most widely used techniques to investigate the neurodynamics of cognitive functions [ 17 20 ], which are especially sensitive to mental fatigue [ 3 , 9 ]. Since the small-world characteristic [ 21 ] and scale-free property [ 22 ] of complex networks were proposed, the studies of complex network topology have entered a high-speed developing period [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, protecting the structural integrity of CA1 and CA3 regions is beneficial to increase the number of surviving neurons and thus improve learning and memory. In recent years, both basic research and clinical practice have shown the advantages of acupuncture in the treatment of cognitive impairment, for example, in a randomized controlled trial, acupuncture treatment slowed cognitive decline and enhanced hippocampal functional connectivity (FC) (Li et al, 2020 ), showing long-term effects of acupuncture on cognitive impairment. The five new keywords that have emerged in recent years are: protocol, pain, injury, diagnosis and guidelines, it indicates that research on this topic is gradually moving toward more systematic, standardized trial protocols and guidelines.…”
Section: Discussionmentioning
confidence: 99%